2016
DOI: 10.1002/mren.201600017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Treatment of Montmorillonite on “Support-Activator” Performance to Support Metallocene for Propylene Polymerization Catalyst

Abstract: This work is focused on montmorillonite (MMT)‐based “support‐activators” (S‐As) for the metallocene‐catalyzed propylene polymerization. This catalyst was previously industrialized; however, for further technological advances, the activation mechanism is investigated. The chemical and morphological requirements of the S‐A are surveyed using both commercially available raw clay minerals (non‐acid‐treated) and acid‐treated clay minerals. The S‐A possessing strong‐acid sites (pKa < −8.2) gives a highly active cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Kotohiro et al synthesized new (imido)vanadium(V) complexes for MAO‐free ethylene polymerization . Recently, Tayano et al succeeded to use acid treated montmorillonite as support and activator for propylene polymerization catalysts . Owing to the cation exchange, curling was observed at the edges of the acidified layered silicates but nanocomposite formation via clay exfoliation was not mentioned.…”
Section: Figurementioning
confidence: 99%
“…Kotohiro et al synthesized new (imido)vanadium(V) complexes for MAO‐free ethylene polymerization . Recently, Tayano et al succeeded to use acid treated montmorillonite as support and activator for propylene polymerization catalysts . Owing to the cation exchange, curling was observed at the edges of the acidified layered silicates but nanocomposite formation via clay exfoliation was not mentioned.…”
Section: Figurementioning
confidence: 99%
“…These results suggested that the acid treatment of the montmorillonite has a crucial impact on inducing the catalytic activity. Tayano et al reported that the acid treatment of montmorillonite increased the amount of the acid sites having p k a < –8.2, and these substantial acid sites effectively promoted the activation of zirconocenes as a catalyst for the propylene polymerization . It was likely that the strong acid sites on the montmorillonite formed by the acid treatment reacted with the alkylaluminum compound and formed surface Lewis acidic sites to promote the formation of “real” active species from the α‐ICA‐Ni complex.…”
Section: Ethylene Homo‐ and Co‐polymerization Using Supported Catalystsmentioning
confidence: 99%
“…This also inspired us to find another way to further improve the activity of this catalyst. As a matter of fact, enhanced acidity could be approached by numerous ways, such as the metal oxides mixtures or even direct acid treatment . While introducing solid superacids consisting of sulfated metal oxides is more preferred, as these compounds are endowed with fairly high acidity, which could be maintained even under temperature higher than 500 °C, and the green nature and low corrosion also make them very attractive .…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, enhanced acidity could be approached by numerous ways, such as the metal oxides mixtures or even direct acid treatment. [23][24][25] While introducing solid superacids consisting of sulfated metal oxides is more preferred, as these compounds are endowed with fairly high acidity, which could be maintained even under temperature higher than 500 °C, and the green nature and low corrosion also make them very attractive. [26] The catalytic applications in alkylation, isomerization, esterification, and reduction of NO are extensively studied, and the enhancement effect in vanadium-oxide-based catalysts for methanol oxidation are widely reported.…”
Section: Introductionmentioning
confidence: 99%